FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN PENGGUNAAN ALAT PELINDUNG DIRI (APD) PERAWATPADA MASA PANDEMI COVID-19 DI INSTALASI GAWAT DARURAT RUMAH SAKIT UMUM DAERAH dr. ZUBIR MAHMUD - Putri Nahrisah; Arista Ardila Arista Ardilla (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2021)
Hospital Occupational Health and Safety (K3RS) are all activities to ensure and protect the safety and health of hospital human resources, patients, patient companions, visitors, and the hospital environment through efforts to prevent work accidents and occupational diseases in hospitals. This study aims to determine the factors related to compliance with the use of personal protective equipment (PPE) for nurses during the COVID-19 pandemic in the ER RSUD dr. Zubir MahmudÂ  2021. The research design used was a quantitative design with a cross sectional approach. The population is all nurses who work in the ER dr. Zubir Mahmud as many as 29 and the sample in this study as many as 29 respondents. Collecting data using a questionnaire. Data analysis using Chi-Squre and looking at Fisher's Exact Test. The results of research on the bivariate test show that there is a significant influence on the independent variables, namely the knowledge factor (p-value = 0.008), attitude (p-value = 0.006), availability (p-value =0.000) and supervision (p-value =0.001). and there was no significant effect, namely the education factor (p-value = 0.622) and years of service (p-value = 0.139) with the dependent variable being the compliance with the use of personal protective equipment (PPE) by nurses during the Covid-19 pandemic.Suggestions in this study are hospitals must make clear SOPs about the use of PPE and increase vigilance during the pandemic.